(untitled) - International Conference on Business History 16 (Tokyo, 1990)
This book represents more than the official proceedings of the conference, rather, would like to this book is the result of extended cooperation bettween committee and the participants.
Keywords: Doanh nghiệp kinh doanh quốc tế,International business enterprises; Lịch sử,History; Nhật Bản,Japan